Design of Audiosonic Frequency Wave Therapy Tool With Arduino Mega-Based Spectrum Analyzer Monitoring - Florentinus Budi Setiawan; Daniel Danin Prasetyo; Leonardus Heru Pratomo (PROtek : Jurnal Ilmiah Teknik Elektro, 2023)
As technology develops, more and more devices can produce or record sound waves. There are currently a lot of sound wave generators in use; however, the frequency output range of these generators is highly constrained. This study is being done to help doctors or the general public treat specific illnesses or disorders such as neurological disorders, headaches, and stomach digestion issues. This prototype was created using experimental or lab techniques. by running tests on the variables being utilized. The Arduino Mega 2560 microcontroller is used to operate this prototype. The Arduino Mega 2560 employs the C and C+ programming languages for its code. The Arduino Mega 2560 may be used to modify the keypad's output frequency, amplitude, and data input. This tool is designed to be able to output frequencies of 20 Hz to 20,000 Hz (human sound). In this study, it has an output in the form of frequencies produced from speakers with test frequencies, namely 200 Hz, 10 kHz, and 17 kHz